2000
DOI: 10.1046/j.1440-1592.2000.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic effect of apple polyphenol on patients with atopic dermatitis: A pilot study

Abstract: The aim of the present study was to evaluate the anti‐allergic effect of apple condensed tannins (ACT) in patients with atopic dermatitis (AD) as a pilot study. An ACT supplement given to the patients at oral doses of 10 mg/kg per day for 8 weeks reduced the inflammation, lichenification, cracking, itching, sleep dis‐ turbance and peripheral blood eosinophil counts. Itching and sleep disturbance scores after ACT supplement even for 2 weeks were significantly decreased compared with the control group. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…The subjects had a mean serum total cholesterol level of 227. 8 2.01 mg/dL. There were no significant differences among the four groups in baseline characteristics ( Table 1).…”
Section: Subjectsmentioning
confidence: 84%
“…The subjects had a mean serum total cholesterol level of 227. 8 2.01 mg/dL. There were no significant differences among the four groups in baseline characteristics ( Table 1).…”
Section: Subjectsmentioning
confidence: 84%
“…A small part of them are utilized as ingredients for animal feed and fertilizer, although this practice poses some environmental and ecological problems (Sudha et al, 2007). Unripe apples contain fairly high levels of polyphenol (Adil et al, 2007;Sudha et al, 2007), which has been reported to have various physiological functions including anti-allergic activity (Kojima et al, 2000;Akiyama et al, 2005), anti-cancer activity (Yanagida et al, 2000), and anti-arteriosclerosis activity (D'Angelo et al, 2007). Some of the agricultural solid by-products like fruit pomace and peel had also been studied for their potential exploitation because of the high contents of polyphenol (Makris et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Key words: allergy; apple polyphenol; Fc"RI; IgE; procyanidin Apple extracts termed ''crude apple polyphenol (CAP)'' and ''apple condensed tannin (ACT)'', which were prepared from immature apples and contained polyphenols as the main component (over 93%), 1) had an anti-allergic effect on patients with atopic dermatitis 2) and on allergic model mice 3) in vivo. The main polyphenols of these apple extracts are procyanidins which are polymers of catechins.…”
mentioning
confidence: 99%